2014
DOI: 10.1186/1756-0500-7-39
|View full text |Cite
|
Sign up to set email alerts
|

A huge renal cyst mimicking ascites: a case report

Abstract: BackgroundRenal cysts are common in old patients, and usually remain untreated. Giant renal cyst measuring more than 15 cm in diameter and containing more than 1500 mls of serous fluid are rarely seen. We report a case of a 75-year-old man with a giant right renal cyst.Case presentationA 75-year-old man presented with a five years history of suprapubic pain, abdominal distension. He had no urological symptoms. Physical examination revealed a distended abdomen with shifting dullness. Routine hematology, biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…The safety of draining huge renal cysts has not yet been established, because there have only been a few reports about drainage of cysts measuring more than 15 cm in diameter. Riyach et al [ 11 ] reported the removal of 8 L of fluid from a giant cyst (35 × 32 × 22 cm) with no major complications.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of draining huge renal cysts has not yet been established, because there have only been a few reports about drainage of cysts measuring more than 15 cm in diameter. Riyach et al [ 11 ] reported the removal of 8 L of fluid from a giant cyst (35 × 32 × 22 cm) with no major complications.…”
Section: Discussionmentioning
confidence: 99%
“…Without ancillary investigations, misdiagnosis of giant renal cysts is common [1][2][3][4][5]. This is often because these lesions are not associated with any pathognomonic symptoms and signs.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 2/3 rd of humans have a kidney cyst detectable by CT scan by the age of 80 years [2]. Majority of these cysts are less than 2cm in size, benign, asymptomatic and treated conservatively [4]. However, giant renal cysts greater than 15cm or containing more than 1500mls of fluid are rare [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most benign renal cysts are asymptomatic and require no treatment. However, cases of huge renal cysts have been very rarely reported [2]. Hodgkin lymphoma is a rare B-cell malignant neoplasm affecting approximately 9000 new patients annually, most patients with Hodgkin lymphoma present with supradiaphragmatic lymphadenopathy, retroperitoneal and inguinal lymphadenopathy occur less frequently [3].…”
Section: Introductionmentioning
confidence: 99%